Bridging the Research and Cultural-Practice Gap in Early Language Intervention in Malaysia - Deborah, Xinyi Yong; Tze-Peng, Wong (Penerbit UKM, 2015)
“Following the child’s lead” and “collaborative consultation with parents” are solidly grounded in the best practice of early language intervention. However, the success of these two practices are based on assumptions that they are valued by families and that they can be feasibly implemented by the attending speech-language pathologist (SLP). Such assumptions can be unjustified in cultures that value the use of “adult-guided instructions” over following the child’s lead and when the work setting of the SLP does not readily accommodate those practices. This article takes the form of a position paper. Through review of the literature, the paper (1) identifies the research-cultural practice gap in early language intervention in Malaysia; (2) positions the two research-informed practices – following the child’s lead and collaborative consultation with parents, on the continuum of intrusiveness in early language intervention; and (3) proposes the techniques of Milieu Teaching as an approach to bridge the research-cultural practice gap in Malaysia.